Survival Foreign Language Acquisition Strategies During the Emergency Remote Learning: An Exploratory Study in Molding Indonesian Students’ Creativity - Mufidah, Nida; Yansyah; Jumadi (Frontiers in Education, 2022)
Being a foreign language, mastery of English acquisition is hard for Indonesian learners. The transformation of teaching and learning in the condition of the COVID-19 outbreak even makes the teaching-and-learning is more difficult since they previously rely on face-to-face interaction and listening to teachers as the primary source of learning with unconvincing result. This article explores how undergraduate students cope up with emergency remote learning. Using exploratory research design, the students learning strategies are identified. Sixty-four university students who experienced blended learning using Google Classroom for one semester were recruited to participate in the research. A questionnaire and interview were used to collect the data. The questionnaire was developed to examine the kinds of effective strategies employed by the students. The interview aimed to detail their responses so their strategies can be mapped clearly. The research findings showed that some learning strategies, such as social and cognitive strategies, are more favorable than others during the pandemic. The condition requires them to make some changes; even some students found some new techniques for learning. At the end of the article, some implications for implementing future blended or online learning are highlighted.